BLOODGROUP AFFILIATION IN MELANOMA MALIGNA PATIENTS: BLOODGROUP AFFILIATION IN MELANOMA MALIGNA PATIENTS - Todorov, Velislav; Boichev, Milen; Minkov, Tzvetan; Georgiev, Volodia; Paraskova, Nadejda; Boycheva, Maria (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
130 patients (66 male and 64 female) suffering from Melanoma maligna are studied. The connection between the illness and the blood group affiliation according to the ABO systems and the Rh. factor is traced. Most of the patients belong to 0 blood group (39,23%), followed by A (23,25%), B (19,38%) and AB (18,14%) group. The significance of group O (p<0,05) and AB (p<0,001) is considerable. The results show a considerable decrease in the percentage of A group (p<0,05) and of the negative Rh. factor (p<0,001). On the basis of the results obtained we can admit that belonging to 0 and AB groups and the positive Rh factor appear to be a part of the hazardous factors for the illness Melanoma maligna and its development.